Foreword from Chair of EECSI 2016 - Imam Much Ibnu Subroto (IAES Indonesia Section, 2016)
In the name of Allah, the Gracious Most Merciful It is great pleasure to welcome out colleagues from all over the world to attend 3rd International Conference on Electrical Engineering, Computer Science, and Informatics (EECSI 2016) Conference in Semarang City, Central Java, Indonesia EECSI 2016 provides a forum for researchers, academicians, professionals, and students from various engineering fields and cross-disciplinary working or interested in the field of Electrical Engineering, Computer Science, and Informatics especially: Power Engineering, Power Systems and Protection; Electric Power Transmission and Distribution; High Voltage Engineering and Insulation Technology; Renewable Energy Sources, Smart-grids Technologies & Applications; Energy: Policy, Security, Infrastructure, Growth and Economics; Power Electronics and Drives; Control, Automation, Instrumentation and Robotics; Information, Internet of Things and Internet Technologies; Electromagnetic Waves and Field; Circuits and Systems; Semiconductors and Applications; Microelectronics and Electronics Technologies; Electronics and Photonics; Wireless Telecommunications and Networking; Remote Sensing and Data Interpretation; Signal, Image, Video & Multimedia Processing; ICT for Electrical and Electronics Applications; Computer Network & Information Security; High Performance Computing and Communication; Databases, Data Mining and Software Engineering. ....